2023
DOI: 10.3390/pr11102810
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of FDM PLA Polymer 3D Printing Technology Based on Tolerance Fields

Ivan Grgić,
Mirko Karakašić,
Hrvoje Glavaš
et al.

Abstract: Fused deposition modelling (FDM) 3D printers have the highest annual growth of 21.15% in the field of 3D printing. FDM desktop 3D printers account for 23.69% of FDM printers. The major drawback of FDM desktop printers is product accuracy, which is particularly pronounced when dimensionally inaccurate and multi-part printed products need to be fit together into a functional assembly. The research presented in this paper aims to determine the accuracy limits of FDM 3D printers when producing elements for assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…An increase in temperature causes a decrease in the strength of the melt and a decrease in the viscosity of the mortar. According to previous sources [ 30 ], with the decrease in viscosity, the outflow from the nozzle increases, and this factor has an effect on the quality of printing. In addition, with the increase in temperature, the strength of the layers increases and a higher printing speed can be used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in temperature causes a decrease in the strength of the melt and a decrease in the viscosity of the mortar. According to previous sources [ 30 ], with the decrease in viscosity, the outflow from the nozzle increases, and this factor has an effect on the quality of printing. In addition, with the increase in temperature, the strength of the layers increases and a higher printing speed can be used.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a negative value decreases the outside dimensions if the printed model exceeds the anticipated size. The EP parameter serves as a means to fine-tune the printed parts and maintain the desired dimensional accuracy [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to [ 28 ], one of the main disadvantages of FFF/FDM prototyping techniques is their low dimensional accuracy. This issue affects the structure in various ways and at different times.…”
Section: Practical Development Of the Dronementioning
confidence: 99%
“…For the first of these, Figure 11 shows the printing process of the base part, both during the process where the internal structure of this part can be observed and after the process has been completed. According to [28], one of the main disadvantages of FFF/FDM prototyping techniques is their low dimensional accuracy. This issue affects the structure in various ways and at different times.…”
Section: The Prototyping and Assembly Of The Modelmentioning
confidence: 99%
“…On further analysis of the experimental data, when only the nozzle diameters of 0.4 mm, 0.6 mm and 0.8 mm were varied and the other factors were kept constant (same material, same sample thickness and same internal configuration), it was concluded that about 80% of the maximum absorption coefficient values were obtained with the 0.4 mm nozzle diameter and 20% of the maximum values were obtained for the 0.6 mm nozzle diameter. Thus, it can be stated that another important aspect regarding the FFF process was the correct choice of the deposition layer height (0.2 mm), which is recommended to not exceed the print nozzle diameter (0.4 mm) in order to obtain good mechanical and acoustic performance [49][50][51]. Figure 5 plots the influence of the sound transmission loss (STL) as a function of the 3D-printed sample.…”
Section: Influence Of Nozzle Diameter On Acoustic Performance Of 3d-p...mentioning
confidence: 99%